A Study on David Ricardo's Economic Philosophy - Agustino, Rinto; Susilastuti, Darwati (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
This study aims to describe and analyze the economic philosophy of David Ricardo, who played a pivotal role in transforming economics into an empirical and positivist discipline. Ricardo shifted the approach of economics from speculative theories not based on facts to a science grounded in empirical data and real-world experience. This research highlights how Ricardo identified and explained the economic activities taking place in society during his time. The findings show that Ricardo eliminated unfounded speculation and focused on actual empirical realities, making economics more objective and measurable. These results confirm that Ricardo successfully moved economics away from speculation and toward a data-driven approach.